City Of Sisterly And Brotherly Loves : Lesbian And Gay Philadelphia, 1945-1972 - Stein, Marc (Book collections on Project MUSE., 2004)
Marc Stein's City of Sisterly and Brotherly Loves is refreshing for at least two reasons: it centers on a city that is not generally associated with a vibrant gay and lesbian culture, and it shows that a community was forming long before the Stonewall rebellion. In this lively and well received book, Marc Stein brings to life the neighborhood bars and clubs where people gathered and the political issues that rallied the community. He reminds us that Philadelphians were leaders in the national gay and lesbian movement and, in doing so, suggests that New York and San Francisco have for too long.